2020
DOI: 10.1177/1758155920963200
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, distribution and relative abundance of avifauna at Ansas Dam and surrounding farmland site Debre Berhan Town, Ethiopia

Abstract: The diversity, distribution, and relative abundance of avifauna were studied at and Around Ansas Dam, Debre Berhan Town, Ethiopia, from early September 2018 to early February 2019, covering both wet and dry seasons. Line transect technique was employed to study the diversity, abundance and distribution of birds species in the farmland site while total count employed on the dam. Data were collected in both wet and dry seasons from 6:30 to10:00 early morning and 15:30 to 18.00 late afternoon, when birds are more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 23 publications
2
13
1
Order By: Relevance
“…In this study, order Passeriformes (67.3%) had the highest number of species from a total of 50 bird species recorded. The result was similar to Shiferaw and Yazezew [34] who surveyed avifauna at Ansas Dam and the surrounding farmland at Debre Berhan Town, Ethiopia. They found a total of 45 bird species belonging to nine orders likewise Passeriformes (37.8%) was represented the highest number.…”
Section: Discussionsupporting
confidence: 85%
“…In this study, order Passeriformes (67.3%) had the highest number of species from a total of 50 bird species recorded. The result was similar to Shiferaw and Yazezew [34] who surveyed avifauna at Ansas Dam and the surrounding farmland at Debre Berhan Town, Ethiopia. They found a total of 45 bird species belonging to nine orders likewise Passeriformes (37.8%) was represented the highest number.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, Mola et al [36] reported that the distribution and abundance of many bird species is determined by the vegetation structure. [30,37] say that the lowest species richness and abundance were observed in forest habitats than in farms and settlements. According to their reasons, in natural forest in their study area, the vegetation composition is low; as a result, only specialist bird species live there.…”
Section: Discussionmentioning
confidence: 99%
“…Te order Passeriformes is the most dominant order that contains 18 families and 37 species in the study area. Similarly, bird species under Passeriformes order are dominant in the other studies [20,[29][30][31]. Most bird species are recorded in the order Passeriformes due to the rapid evolution of Passerine species and their adaptation to all terrestrial environments and the presence of a large number of species [32].…”
Section: Discussionmentioning
confidence: 99%
“…e Washa site is also located at 9 °39′45″ latitude and 39 °32′45″ longitude, whereas the Borale site is situated at 9 °39′62″ latitude and 39 °32′36″ longitude. e temperature of DBT ranges from the mean annual minimum to maximum temperature of 2.3 °C to 22 °C, respectively, and its mean annual rainfall is 906 mm [14]. In 01 Kebele, about 690 total households were living, of whom 149 and 58 households of Borale and Washa sites, respectively, had been irrigated land downstream/around and cultivated various vegetable and cereal crops at least twice a year by extracting water directly from the reservoirs (interviews made with experts of Urban Agricultural Office of DBT).…”
Section: Description Of the Study Areamentioning
confidence: 99%
“…Still, no spiritual service was provided at all by Borale, except very low by Washa. is is because the Washa Wetland is endowed with a variety of natural attractions and is preferred by endemic birds [14], whereas the Borale site was highly impaired and less accessible. However, tourism benefits from such wetlands (1) if they get attention.…”
Section: E Relative Importance Of the Essmentioning
confidence: 99%